Viral persistence in colorectal cancer cells infected by Newcastle disease virus - Chia, Suet Lin; Yusoff, Khatijah; Shafee, Norazizah (BioMed Central, 2014)
Background Newcastle disease virus (NDV), a single-stranded RNA virus of the family Paramyxoviridae, is a candidate virotherapy agent in cancer treatment. Promising responses were observed in clinical studies. Despite its high potential, the possibility of the virus to develop a persistent form of infection in cancer cells has not been investigated. Occurrence of persistent infection by NDV in cancer cells may cause the cells to be less susceptible to the virus killing. This would give rise to a population of cancer cells that remains viable and resistant to treatment. Results During infection experiment in a series of colorectal cancer cell lines, we adventitiously observed a development of persistent infection by NDV in SW480 cells, but not in other cell lines tested. This cell population, designated as SW480P, showed resistancy towards NDV killing in a re-infection experiment. The SW480P cells retained NDV genome and produced virus progeny with reduced plaque forming ability. Conclusion These observations showed that NDV could develop persistent infection in cancer cells and this factor needs to be taken into consideration when using NDV in clinical settings.